All Days 2014
DOI: 10.2118/172359-ms
|View full text |Cite
|
Sign up to set email alerts
|

PVT Fluid Characterization and Consistency Check for Retrograde Condensate Reservoir Modeling

Abstract: Retrograde gas condensate systems are complex systems as a result of the unique compositional changes that when the reservoir pressure is decreased. Correct selection of Equation of State (EOS) is necessary for proper fluid characterization so that the PVT behavior in the simulation model is a good representation of the reservoir fluid. High quality and accurate PVT data can reduce uncertainty in reservoir fluid properties and set the stage for reservoir engineering modeling whilst improving the technical work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…For measuring the solubility parameter of live oil samples while considering the effect of pressure and temperature, internal pressure appears to be the most relevant method to be used [33]. Internal pressure (π) is defined as follows [33][34][35]: (2) where is coefficient of isobaric expansion of oil (1/K), and is coefficient of isothermal compressibility of oil (1/Pa, 1/MPa), T is temperature (K), and P is pressure (Pa, MPa). Both internal pressure and solubility parameter describe the same phenomenon, the cohesion of a liquid, but not in the same way [35].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For measuring the solubility parameter of live oil samples while considering the effect of pressure and temperature, internal pressure appears to be the most relevant method to be used [33]. Internal pressure (π) is defined as follows [33][34][35]: (2) where is coefficient of isobaric expansion of oil (1/K), and is coefficient of isothermal compressibility of oil (1/Pa, 1/MPa), T is temperature (K), and P is pressure (Pa, MPa). Both internal pressure and solubility parameter describe the same phenomenon, the cohesion of a liquid, but not in the same way [35].…”
Section: Methodsmentioning
confidence: 99%
“…Inaccurate fluid analysis can seriously affect all facets of chemical and petroleum engineering such as fluid properties measurement and construction of thermodynamic model for representative reservoir fluid, precise evaluation of hydrocarbon in place (i.e. amount of hydrocarbon likely to be contained in the reservoir), and reservoir development strategies [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Buckley has shown that log (K i ) versus T c 2 yields a straight line with negative slope. Therefore, any observed deviations from the straight line in the Buckley plot illustrate existing of the composition measuring errors (Whitson and Brulé 2000;Akpabio et al 2014Akpabio et al , 2015. Modified Wilson plot is another thermodynamic method which could be applied for checking the fluid compositions reliability.…”
Section: Thermodynamic Consistency Check Of Compositionmentioning
confidence: 99%
“…[40] This form of the interaction potential function behaviour is consistent with that of an isothermal process and can be appropriately applied for density ratios $7-8, which we deal with here. [32,44,50,51] In LB modelling, the macroscopic fluid density and velocity can be obtained using the fluid distribution functions. [40] To calculate the pressure throughout the domain, an equation of state (EOS) is required to be employed.…”
Section: Single Component Multi-phase Modelmentioning
confidence: 99%
“…There are various forms of the interaction potential proposed by Raiskinmäki et al, Hyväluoma et al, Martys and Chen, and Qian et al Here, we used the ψ function introduced by Shan and Chen as follows: ψtrue(ρtrue)=ψ0 exptrue(ρ0ρtrue) where ψ0 and ρ0 are arbitrary constants . This form of the interaction potential function behaviour is consistent with that of an isothermal process and can be appropriately applied for density ratios ∼7–8, which we deal with here …”
Section: Lb Mathematical Modelmentioning
confidence: 99%